Химическая технология золота и серебра: учебное пособие - Оствальд Р. В. Роман Вячеславович; Пашков А. А. Александр Алексеевич; Леонова Л. А. Лилия Александровна (Томск, Изд-во ТПУ, 2021)
Заглавие с титульного экрана